Neglected Risk in Financial Innovation: Evidence from Structured Product Counterparty Exposure. (30th July 2020) - Arnold, Marc; Schuette, Dustin; Wagner, Alexander
Abstract: We investigate the compensation of counterparty exposure in the prices of structured products. Our analysis reveals that product issuers did not compensate retail investors for counterparty exposure before the Lehman default. Post‐Lehman, retail prices have no longer neglected this risk. We also measure retail investor attention towards issuer credit risk. For a given level of issuer credit risk, counterparty exposure is compensated more when attention is higher. Furthermore, issuers tend to construct products with larger counterparty exposure. Overall, our results shed light on the conditions under which financial engineering generates neglected risk.